Summary From the First Kidney Cancer Research Summit, September 12–13, 2019: A Focus on Translational Research. Issue 3 (2nd May 2020) - Choueiri, Toni K; Atkins, Michael B; Bakouny, Ziad; Carlo, Maria I; Drake, Charles G; Jonasch, Eric; Kapur, Payal; Lewis, Bryan; Linehan, W Marston; Mitchell, Michael J; Pal, Sumanta K; Pels, Kevin; et al.
Abstract: Kidney cancer is one of the 10 most common cancers both in the United States and worldwide. Until this year, there had not previously been a conference focused on translational studies in the broad and heterogeneous group of kidney cancers. Therefore, a group of researchers, clinicians, and patient advocates dedicated to renal cell carcinoma launched the Kidney Cancer Research Summit (KCRS) to spur collaboration and further therapeutic advances in these tumors. This commentary aims to summarize the oral presentations and serve as a record for future iterations of this meeting. The KCRS sessions addressed the tumor microenvironment, novel methods of drug delivery, single cell sequencing strategies, novel immune checkpoint blockade and cellular therapies, predictive biomarkers, and rare variants of kidney cancers. In addition, the meeting included 2 sessions to promote scientific mentoring and kidney cancer research collaborations. A subsequent KCRS will be planned for the fall of 2020.